1981
DOI: 10.1079/bjn19810072
|View full text |Cite
|
Sign up to set email alerts
|

The effect of meal frequency and protein concentration on the composition of the weight lost by obese subjects

Abstract: . 1.Nitrogen balance, weight loss and resting metabolic rate were measured in thirty-eight obese inpatients on 2. All subjects were fed on 13% protein-energy in three rneals/d for the first week. 3. In weeks 2 or 3, using a cross-over design, ten subjects were fed on 15 or 10% protein-energy as three rneals/d; fourteen subjects were fed on five or one meal/d with 13%proteinenergy; and fourteen subjects were fed on 15% protein-energy as five mealsld or 10% protein-emergy as one meal/d. 4. N loss was least on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…Nitrogen loss was greater when obese individuals were fed 1 vs. 5 meals/d and when fed 10% vs. 15% protein. Of note, these effects were additive [65]. Similar trends were observed in a subsequent study by Arciero et al [66].…”
Section: Does Increasing Meal Frequency Impact Body Weight Managementsupporting
confidence: 86%
“…Nitrogen loss was greater when obese individuals were fed 1 vs. 5 meals/d and when fed 10% vs. 15% protein. Of note, these effects were additive [65]. Similar trends were observed in a subsequent study by Arciero et al [66].…”
Section: Does Increasing Meal Frequency Impact Body Weight Managementsupporting
confidence: 86%
“…In this case, the failure to ®nd a signi®cant difference in total energy expenditure with meal frequency suggests that any change in NEAT was small or there was a concurrent change in diet-induced thermogenesis or basal metabolic rate which is not supported by the literature (diet-induced thermogenesis; 11,18 resting metabolic rate 19 ). We did, however, ®nd a lag in energy expenditure with two meals per day compared with six meals per day demonstrated by the signi®cantly higher energy expenditure during the`night phase'.…”
Section: Discussionmentioning
confidence: 77%
“…On the other hand, snacking between meals may not be satiating (Booth, 1988;Marmonier et al, 2002) and therefore, habitual snacking may be a factor driving energy intake up and instead increase body weight. Although, short experimental studies in obese subjects have not shown any effect of eating frequency on weight loss in energy-restricted diets (Garrow et al, 1981;Verboeket-van de Venne and Westerterp, 1993), epidemiological studies suggest a link between snacking and weight gain (Basdevant et al, 1993;Coakley et al, 1998;Levitsky et al, 2004). Subjects who regain weight after successful weight reduction also report more snacks than those who maintain their weight loss (Kayman et al, 1990).…”
Section: Introductionmentioning
confidence: 99%